PENGARUH LAYANAN PENDIDIKAN AGAMA DI SEKOLAH TERHADAP RELIGIUSITAS SISWA Studi expost facto di Medan - suhardin hardin din (Diglosia : Jurnal Pendidikan, Kebahasaan, dan Kesusastraan Indonesia, 2017)
The objective of this research to find out the effect of the level religious educational service with religiusitas student. The research was conducted in SMA/SMK Goverment and non Goverment in the  Medan Nort Sumatera  using 1X2  design involving 22 school chosen by using purposive random sampling. The data analysis and interpretation indicated that: There is  not difference religiusitas volue student in the school have religious educational service high between  the school have religious educational service low. The conclusion the level school have religious educational service not effect againt religiusitas student volue. Keywords: religious, religiusitas student, religius educational service.